The Correlation between Neutrophil-to-Lymphocyte Ratio with C-reactive Protein and D-dimer Level among Indonesian COVID-19 Cases - Rotty, Linda; Kurube, Jerome; Harijanto, Paulus Novian; Wantania, Frans; Haroen, Harlinda; Hendratta, Cecilia; Lasut, Pearla; Kawengian, Christian; Adiwinata, Randy (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Coronavirus disease-19 (COVID-19) pandemic has resulted high number of mortalities globally. Several inflammatory and coagulation biomarkers have been studied for predicting and differentiating severe COVID-19 such as C-reactive protein (CRP) and D-dimer. However, those markers may not readily available in developing countries. AIM: The aim of the study was to assess the utility of neutrophil-to-lymphocyte ratio (NLR), a widely available and inexpensive laboratory examination, as reliable inflammatory biomarkers for Indonesian COVID-19 patients; by analyzing the correlation of NLR level with CRP and D-dimer plasma level. METHODS: We conducted cross-sectional study in Professor Dr. R.D. Kandou Hospital, Manado involving RT-PCR confirmed and hospitalized COVID-19 patients. Lymphocyte count, NLR, CRP, and D-dimer were examined in severe and non-severe COVID-19 cases at hospital admission. Correlation test was done using Spearman correlation test. RESULTS: A total of 40 COVID-19 patients were included in the analysis, with 50% having mild disease and other half having severe disease. The NLR, CRP, and D-dimer were significantly higher in severe COVID-19 group. Significant correlation was found between NLR and CRP (p = 0.001 and r = 0.506) and also with D-dimer level (p = 0.000 and r = 0.570) in differentiating severity of COVID-19. CONCLUSION: NLR is correlated with CRP and D-dimer level; therefore, NLR may serve as reliable, cost-effective, and practical inflammatory biomarker for differentiating severe and non-severe COVID-19 cases.